2019
DOI: 10.1590/s1980-220x2018015903465
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nurse education and training on communication, emotional intelligence, and empathy

Abstract: Objective: To determine the influence of nurse education and training on attitudes towards communication, emotional intelligence, and empathy. Method: A crosssectional study was conducted using three separate instruments to measure attitudes towards communication, empathy, and emotional intelligence, and two questions to determine the academic qualifications of the study participants. The effect of the variables was tested using one-way ANOVA, Pearson correlations, and hierarchical multiple linear regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
1
15
0
5
Order By: Relevance
“…A person's education level can also affect communication. This result in line with previous study that level of education promotes the ability of nurses to communicate effectively to ensure service quality (Prado-Gasco et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…A person's education level can also affect communication. This result in line with previous study that level of education promotes the ability of nurses to communicate effectively to ensure service quality (Prado-Gasco et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Related research has suggested that empathy is an aspect of emotional intelligence. In addition, emotional intelligence also consists of self-awareness, self-motivation, and mental management [39]. Emotional intelligence has shown a positive predictive effect on communication satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…15 Prioritizing specialized training programs in communication, emotional intelligence, and empathy can also enhance teamwork and service quality. [22][23][24]…”
Section: Discussionmentioning
confidence: 99%